Judaism of the second temple period. Volume 1. Qumran and apocalypticism, David Flusser : book review - Naudé, Jacobus A. (Old Testament essays, 2008)
David Flusser (1917-2000) was professor of early Christianity and Second Temple Judaism at the Hebrew University of Jerusalem and a prolific scholar of the Dead Sea Scrolls. He was especially influential in Israeli scholarship. Flusser conversed fluently in nine languages and read scholarly literature in an additional seventeen. His first language was German. His second, learned fluently only after his immigration to Israel, was Hebrew. Consequently, most of Flusser's published writings are in German or Hebrew. They were widely scattered in obscure publications. Only a small percentage of Flusser's articles were authored in English. With this English translation by Azzan Yadin of his collected essays in Hebrew (2002), Flusser's insights are now available to a wider audience than ever before. It discusses many aspects of the relation of Qumran literature to later Jewish writings and even to the Christian writings of the New Testament.